A Comprehensive Systematic Review Comparing Perioperative Outcomes of Robotic-Assisted versus Laparoscopic Resection of the Anterior Liver Segments - Dita Oktaviani Ayuningtyas; Ika Fitriana Setyaningtias (International Medical Journal Corp. Ltd, 2026)
Introduction: Minimally invasive liver surgery (MILS) is the contemporary standard for lesions in the anterior liver segments (II, III, IVb, V, VI), where the parenchymal transection plane is directly accessible. Robotic advantages in posterosuperior segments and major hepatectomy are established, yet its incremental value in the comparatively